(untitled) (Biological Sciences - PJSIR, 1998)
Three moisture levels viz. 70, 80 and 90% soil moisture depletion (SMD) and two NP levels i.e. 75-50 and 150-75 kg ha were studied for maize crop. Irrigation water was computed by gravimetric measurement and irrigation method applied. The consumptive use of water (551 mm) gave the highest grain yield of 4.66 tons ha" when irrigated at 80% SMD with high fertility level i.e. 150-75 kg ha’. Grain yield was significantly affected by soil moisture and fertility levels. The highest water use efficiency (ECWU) was 8.45 kg mm’ when crop was irrigated at 80% SMD. The average evapotranspiration per day ( Eta day") for the whole growing season was 4.93, 4.34 and 3.87 mm at 70, 80 and 90% SMD, respectively.